(untitled) (Panauti Journal, 2025)
Landlessness and persistent agrarian inequalities in Nepal continue to shape rural poverty, reflecting the enduring effects of historical land tenure systems, social hierarchies, and uneven policy implementation. The purpose of this study is to examine how landlessness reproduces rural inequality in Nepal by exploring the historical, social, economic, and geographic factors that shape access to land and its consequences for poverty and social exclusion. Findings show that landlessness remains the key driver of rural inequality in Nepal, with smaller landholdings directly linked to higher poverty, deepening structural marginalization, and compounded vulnerabilities for women, Dalits, and indigenous communities. The research also identifies future avenues for exploring intergenerational landlessness, migration, and the effectiveness of reforms to promote inclusive rural development in Nepal.